A regioregular donor–acceptor copolymer allowing a high gain–bandwidth product to be obtained in photomultiplication-type organic photodiodes. Issue 1 (18th November 2020) - Kim, Juhee; So, Chan; Kang, Mingyun; Sim, Kyu Min; Lim, Bogyu; Chung, Dae Sung
Abstract : A newly synthesized regioregular donor polymer is used in photomultiplication-type organic photodiodes (PM-OPDs), and its regioregularity enables face-on orientation with a low trap density, leading to a high gain and fast response time in PM-OPDs. Abstract : Obtaining a photomultiplication-type organic photodiode with a high gain–bandwidth product is challenging. We show that a newly designed regioregular polymer enables the formation of a highly oriented face-on structure with a low trap density, leading to a high EQE and a fast response time. As a result, a gain–bandwidth product of over 4 × 10 5 Hz is achieved.